Biosynthesis of silver nanoparticles from Syzygium cumini leaves and their potential effects on odontogenic pathogens and biofilms - Bernardo, Wagner Luis de Carvalho; Boriollo, Marcelo Fabiano Gomes; Tonon, Caroline Coradi; da Silva, Jeferson Júnior; Oliveira, Mateus Cardoso; de Moraes, Fernando Cruz; Spolidorio, Denise Madalena Palomari (Frontiers in Microbiology, 2022)
This study analyzed the antimicrobial and antibiofilm action and cytotoxicity of extract (HEScL) and silver nanoparticles (AgNPs-HEScL) from Syzygium cumini leaves. GC-MS, UV-Vis, EDX, FEG/SEM, DLS and zeta potential assays were used to characterize the extract or nanoparticles. Antimicrobial, antibiofilm and cytotoxicity analyses were carried out by in vitro methods: agar diffusion, microdilution and normal oral keratinocytes spontaneously immortalized (NOK-SI) cell culture. MICs of planktonic cells ranged from 31.2-250 (AgNPs-HEScL) to 1,296.8-10,375 g/ml (HEScL) for Actinomyces naeslundii, Fusobacterium nucleatum, Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus mutans, Streptococcus oralis, Veillonella dispar, and Candida albicans. AgNPs-HEScL showed antibiofilm effects (125-8,000 g/ml) towards Candida albicans, Streptococcus mutans and Streptococcus oralis, and Staphylococcus aureus and Staphylococcus epidermidis. The NOK-SI exhibited no cytotoxicity when treated with 32.8 and 680.3 g/ml of AgNPs-HEScL and HEScL, respectively, for 5 min. The data suggest potential antimicrobial and antibiofilm action of HEScL, and more specifically, AgNPs-HEScL, involving pathogens of medical and dental interest (dose-, time- and species-dependent). The cytotoxicity of HEScL and AgNPs-HEScL detected in NOK-SI was dose- and time-dependent. This study presents toxicological information about the lyophilized ethanolic extract of S. cumini leaves, including their metallic nanoparticles, and adds scientific values to incipient studies found in the literature.